2020
DOI: 10.2319/082019-542.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative analyses of orthodontic-related videos on YouTube

Abstract: Objectives To investigate content of orthodontic-related videos on YouTube to improve the understanding of orthodontic patients' perceptions and treatment experiences. Materials and Methods A systematic search was conducted on YouTube on March 20, 2018, and updated on August 4, 2019, to identify all relevant videos using search terms “orthodontic,” “orthodontics,” “braces,” and “orthodontic braces.” The data set was captured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 15 publications
1
29
0
2
Order By: Relevance
“…Thus, we conclude that in our study, results from STM and BERTopic provide information on different hierarchical levels. Indeed, BERTopic's granularity helped to identify highly specialized forms of creative activity, such as constructing an oven and other heat-related aspects (e.g., thermal isolation), or dealing with dental issues, similar to what has been found in a previous study (Guo et al, 2020), which highlight the diversity and idiosyncrasy of everyday creativity. Considering both broad and narrow classifications provided by STM and BERTopic together could eventually guide the development of new inventories by suggesting relevant domains and items, respectively.…”
Section: Topic Modeling With Bertopicsupporting
confidence: 57%
See 1 more Smart Citation
“…Thus, we conclude that in our study, results from STM and BERTopic provide information on different hierarchical levels. Indeed, BERTopic's granularity helped to identify highly specialized forms of creative activity, such as constructing an oven and other heat-related aspects (e.g., thermal isolation), or dealing with dental issues, similar to what has been found in a previous study (Guo et al, 2020), which highlight the diversity and idiosyncrasy of everyday creativity. Considering both broad and narrow classifications provided by STM and BERTopic together could eventually guide the development of new inventories by suggesting relevant domains and items, respectively.…”
Section: Topic Modeling With Bertopicsupporting
confidence: 57%
“…This indicates that viewers discern the degree of effectivity and appropriateness, and these judgements may benefit from seeing the process rather than just seeing the final product. This evaluation is important in light of evidence that there is low quality, in fact, even dubious content available: Guo et al (2020) investigated orthodontic-related videos on YouTube and found DIY videos about creating fake braces or self-removing real ones, and self-treating other dental issues. Consequently, this digital space requires users to discriminate obscure, low-quality content from educational and inspirational videos about creative products.…”
mentioning
confidence: 99%
“…YouTube videos have been evaluated for smile, wisdom tooth surgical removal, dental implants, dental avulsion injuries, root canal treatment, orthognathic surgery, orthodontics, burning mouth syndrome and mouth (oral) cancer [ 12 16 18 19 20 21 25 26 27 28 ]. The majority of these research papers recommended avoidance of this source for educating patients about dental diseases and treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies proposed a system of active reminders for adolescents undergoing orthodontic treatment by weekly text messaging their parents [ 8 , 10 12 ], using WhatsApp chat room for sharing “selfies” of their smile [ 13 ], and using computer-based training to teach Fones brushing technique or modified Bass technique [ 14 ]. In addition, frequently used social media among young subjects, such as Instagram [ 15 ], or other digital platforms, such as YouTube [ 16 ], have shown to improve oral health knowledge among orthodontic patients. Still, some studies found no positive effect of instructions about oral hygiene during orthodontic treatment by using social media-based and messaging apps, respectively [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%